Exploring Students’ Experiences in Using Metacognitive Strategies in Completing Classroom Listening Tasks - Fasya Aristawidya Fauziah As’ari; Muhammad Handi Gunawan (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Listening is often considered one of the most challenging skills for English as a Foreign Language (EFL) learners because it requires learners to process spoken information in real time. Difficulties such as fast speech, unfamiliar accents, and limited vocabulary may affect learners’ ability to understand spoken texts and regulate their comprehension. This study explores how EFL students apply metacognitive listening strategies during classroom listening activities and identify the challenges that influence their strategy use. A qualitative descriptive design was employed to gain deeper insight into students’ experiences. Data were collected from 19 undergraduate students through an open-ended questionnaire reconstructed from the Metacognitive Awareness Listening Questionnaire (MALQ), document analysis, and semi-structured interview. The data were analyzed using theory-driven thematic analysis based on five metacognitive components: planning and evaluation, directed attention, person knowledge, mental translation, and problem solving. The findings reveal that students used all five strategies, but their use was uneven. Problem-solving and directed attention strategies appeared most frequently, while planning strategies were less used. Mental translation was used selectively depending on the listening situation, and students’ self-perceptions and emotional responses influenced their strategic behavior. The study concludes that EFL listening is not only a linguistic process but also a metacognitive and emotional one, suggesting the importance of more explicit metacognitive strategy instruction in listening classrooms.